2022
DOI: 10.1021/acs.biomac.2c01019
|View full text |Cite
|
Sign up to set email alerts
|

A Psychrophilic GelMA: Breaking Technical and Immunological Barriers for Multimaterial High-Resolution 3D Bioprinting

Abstract: The increasing demand for tissue replacement has encouraged scientists worldwide to focus on developing new biofabrication technologies. Multimaterials/cells printed with stringent resolutions are necessary to address the high complexity of tissues. Advanced inkjet 3D printing can use multimaterials and attain high resolution and complexity of printed structures. However, a decisive yet limiting aspect of translational 3D bioprinting is selecting the befitting material to be used as bioink; there is a complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In addition, this study did not perform a detailed evaluation of the biomaterial immune response. However, in a previous study, sGelMA hydrogels presented low immunogenicity after in vivo implantation in a murine model compared with mammalian GelMA hydrogels [32].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, this study did not perform a detailed evaluation of the biomaterial immune response. However, in a previous study, sGelMA hydrogels presented low immunogenicity after in vivo implantation in a murine model compared with mammalian GelMA hydrogels [32].…”
Section: Discussionmentioning
confidence: 80%
“…The lower viscosity of sGelMA, reported in previous laboratory studies [32], allows liquid handling of solutions at far higher concentrations than mammalian GelMA, making it possible to obtain hydrogels with a much higher concentration of polymer. Therefore, two stock solutions with high polymer concentrations were prepared (40% and 50% sGelMA (w/v)) to obtain the different formulations.…”
Section: Fabrication Of Non-porous and Porous Sgelma Formulationsmentioning
confidence: 90%
“…Furthermore, Zaupa et al showed that GelMA hydrogels obtained with salmon and bovine origins displayed similar compression modulus at 40 °C (over gelation temperature for both gelatin types), but different pore sizes at the same degree of functionalization, which increased the cell-remodeling rate, suggesting that salmon GelMA hydrogels present higher molecular mobility [ 36 ]. This particular characteristic of GelMA with a salmon origin has allowed its use for the development of a bioink formulation for its use in high-resolution 3D printing systems such as polyjet 3D printing, showing that this formulation achieved a high viability (∼80%) and proliferation of co-printed cells, while demonstrating in vivo the immune tolerance of printed structures [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 For instance, salmon skinderived gelatin (sGel) possesses less proline and hydroxyproline in its aminoacidic sequence than mammalian gelatins, and consequently, cold-adapted gelatins in solution have a very low-temperature melting point (∼4 °C), unlike mammalian gelatin solutions that melt above 30 °C, allowing for low viscous, highly concentrated, and stable liquid phase solutions at room temperature, properties that cannot be achieved with mesophilic gelatins. [15][16][17] Methacrylated sGel (sGelMA) has demonstrated interesting applications in high-resolution 3D bioprinting due to its injectability properties, 18 allowing the preparation of solutions with high concentrations of the polymer while maintaining the liquid state, making the biofabrication of scaffolds with high resistance to compression plausible for cartilage regeneration applications. Additionally, polymerization could be induced in situ with UV light, allowing the complete filling of a lesion, even for lesions with intricate edges.…”
Section: Introductionmentioning
confidence: 99%
“…Methacrylated sGel (sGelMA) has demonstrated interesting applications in high-resolution 3D bioprinting due to its injectability properties, 18 allowing the preparation of solutions with high concentrations of the polymer while maintaining the liquid state, making the biofabrication of scaffolds with high resistance to compression plausible for cartilage regeneration applications. Additionally, polymerization could be induced in situ with UV light, allowing the complete filling of a lesion, even for lesions with intricate edges.…”
Section: Introductionmentioning
confidence: 99%